“I set the tone”: the role of biological mothers in the successful formation of stepfamilies - Thompson, David E. (Kansas State University, 2009)
ABSTRACT The focus of the present qualitative study was on the specific roles played by mothers in helping the members of their families adjust to each other and successfully transition into a family unit. Mothers play an important role in the lives of their children and their husbands as they form stepfamilies. Utilizing symbolic interaction and family systems theories, all of the members of two stepfamilies were interviewed. Using cross-case analysis, communication, adaptability/ flexibility, positive identity and positive perspective were identified as familial attributes leading to their success as families. Mothers were identified by their husbands and their children as playing essential, pivotal roles in the facilitation of the formation and sustenance of the stepfather/stepchild relationship. Implications of these findings are discussed, along with the contributions of this study to the literature and insights and implications for researchers as well as professionals working with stepfamilies.
Keywords: Stepfamilies; Mothers; Maternal Gatekeeping; Stepfamily Formation; Sociology, Individual and Family Studies (0628)